La inserción del componente investigativo en el proceso enseñanza aprendizaje en Ingeniería Agrónoma (2019)
This article analyzes the process of integrating the research component in the Agronomic Engineering curriculum of the Banes University Center, Cuba, specifically in research methodology. The theoretical - documentary design is based on the analysis of the content of the curriculum of the aforementioned academic offer worked in semiessential conditions. A proactive component is also addressed through the conception of a proposal focused on integrative tasks whose validation is done through expert discussion groups. As a main result, it is worth highlighting that the integrative tasks as the basis of didactic mediation in research methodology, allow contributing to the problematization and professionalization of the contents of the subject in the study plan. Among the conclusions, the need for an interdisciplinary methodological treatment oriented to the objectives of the career is evidenced, in order to favor the development of scientific competences in students.